PEMIMPIN ZALIM DALAM PANDANGAN HADIS: (Suatu Kajian Kritik Hadis pada Riwayat Ahmad bin Hanbal) - Radhie Munadi (AL-Fikr, 2022)
This article discusses the unjust leaders in the view of the hadith of the Prophet Muhammad. In this article, there are several important things that will become the core of the discussion, namely, the definition of an unjust leader, the hadith about the unjust leader, and the content or explanation regarding the hadith of the unjust leader. Therefore, it is necessary to explain these things so as not to cause mistakes and misunderstandings in choosing a leader or becoming a leader. The study of this problem is carried out by conducting a literature review of the hadith of the Prophet Muhammad. So the conclusion is that injustice meets all the criteria, namely an act that harms others or puts something out of place. The wrongdoing is very hated by Allah swt. Because the consequences are detrimental to humans and Allah has honored humans with one another. Keywords; Leader, Zalim, Hadith